Peran pembiayaan syariah pada UMKM terhadap pertumbuhan ekonomi di Indonesia - Nuriyah, Neng Liana Shinta (Maliki Interdisciplinary Journal, 2023)
In recent years, the issue of economic growth has become a complex challenge for Indonesia. In dealing with these problems, there are several factors that can influence economic growth to develop properly. In this situation, Micro, Small and Medium Enterprises have emerged as an important factor that can help Indonesia's economic growth. However, in this case, MSMEs usually face several obstacles such as a lack of capital that can help develop these MSMEs. In this article, the author discusses how sharia financing can help MSMEs in developing their business so that these MSMEs can have an effect on increasing Indonesia's economic growth. This research article uses a qualitative method with a literature study approach, which is a research method that uses data sources from various literature such as books, research articles, official documents, and journals to answer research questions. Based on the results of research that has been carried out by research through a literature study approach, that sharia financing for MSMEs can contribute significantly to Indonesia's economic growth in the long term. Sharia financing can help MSMEs in obtaining business capital needed to develop their business.